THE ROLE OF SERVICE QUALITY, PRICES AND PROMOTIONS ON CUSTOMER SATISFACTION WEDDING ORGANIZER LISKA NGANJUK - Handik Dwi Santoso; Sri Aliami; Susi Damayanti (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The background of this research is that competition for wedding organizers is increasing, so the Liska Nganjuk Backdrop service company can win the competition by consistently delivering higher quality services compared to competitors and higher than customer expectations. Therefore, consumers are now starting to become smarter. and selective in choosing the products and services they will use. This research aims to test and determine the significance of service quality on consumer satisfaction of Wedding Organizer Liska Nganjuk, price on consumer satisfaction of Wedding Organizer Liska Nganjuk and promotion on consumer satisfaction of Wedding Organizer Liska Nganjuk. The research was carried out using a quantitative approach with a sample of 40 respondents, data was collected through distributing questionnaires and analyzed using the classic assumption test, multiple linear regression, coefficient of determination, t test, and f test with SPSS 27 software. The results of this research are (1) service quality has significant influence on consumer satisfaction. (2) price has a significant influence on consumer satisfaction. (3) promotions have a significant influence on consumer satisfaction. (4) service quality, price and promotion simultaneously have a significant effect on Backdrop Liska Nganjuk consumer satisfaction.